Complementary Roles of Nod2 in Hematopoietic and Nonhematopoietic Cells in Preventing Gut Barrier Dysfunction Dependent on MLCK Activity. Issue 7 (July 2017) - Al Nabhani, Ziad; Montcuquet, Nicolas; Roy, Maryline; Dussaillant, Monique; Hugot, Jean-Pierre; Barreau, Frédérick
Abstract : Background: Crohn's disease (CD) pathogenesis is multifactorial involving genetic and environmental factors. Loss of function mutations in the nucleotide oligomerization domain 2 ( NOD2 ) gene are the main genetic risk factor for CD. Like patients with CD, Nod2 KO mice are characterized by an enhanced Th1 immune response and a defective mucosal barrier function evidenced by increased intestinal permeability. We previously showed that the latter is related to hematopoietic Nod2 deficiency. Our aim was to explore the mechanisms by which Nod2 expressed in the hematopoietic and in the nonhematopoietic compartments interplay to control epithelial paracellular permeability. Methods: Depletion of CD4 + T cells in Nod2 KO mice and treatments with inhibitors were conducted in chimeric mice transplanted with bone marrow cells from Nod2-deficient donors into Nod2-sufficient recipients or vice versa. Caco-2 cells overexpressing a NOD2 gene which did or did not include a CD-associated polymorphism were treated with inhibitors or siRNAs and cocultured with hematopoietic cells from Peyer's patches. Results: In vivo and in vitro Nod2 in hematopoietic cells regulates epithelial paracellular permeability through cytokine production influencing myosin light chain kinase (MLCK) activity. Indeed, tumor necrosis factor-α and interferon-γ secretion by CD4 + T cells upregulated expression and activity of epithelial MLCK leading to increased epithelial tight junction opening. When stimulated by muramyl dipeptide, Nod2 in the nonhematopoietic compartment normalized the permeability and T-cell cytokine secretion and regulated MLCK activity. This MLCK regulation is mediated by TAK1 and RICK-dependent mechanisms. Conclusions: Our study demonstrates how hematopoietic and nonhematopoietic Nod2 regulate intestinal barrier function, improving our knowledge on the mechanisms involved in CD pathogenesis. Abstract : Article first published online 16 May 2017.Supplemental Digital Content is Available in the Text.